DIFUSI NATRIUM DIKLOFENAK DALAM GEL METHOCEL 400 PADA BERBAGAI pH - Ketut Widyani Astuti; Yeyet C. Sumirtapura; Ni Nyoman Wiwik S. (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2012)
Diffusion of sodium diclofenac in Methocel 400 gel at various pH has been studied. Diffusion test was performed in diffusion cells with artificial membranes of Whatman no.1 filter paper which was immersed in Spangler solution. Measurement of active ingredient concentration that diffuses was performed using UV spectrophotometer at a wavelength of 277 nm.The results showed that highest diffusion of diclofenac sodium occured at pH 7 with a mean percentage of diclofenac sodium diffuses after 240 minutes of 56,88 + 13,70%. The mean percentage of diclofenac sodium which diffuses from the gel Methocel 400 at pH 6 after 240 minutes was 30,39 + 1,08% while that from the Methocel 400 gel at pH 8 was 46,84 + 6,24%.